The phonetic interaction of prosodic elements in the Baltic languages: a tentative theoretical model - Švageris, Evaldas (Baltistica, 2023)
The aim of this paper is to propose a theoretical model of phonetic interaction between prosodic elements in the Baltic languages. Long syllables, for example, sometimes become the field of the synchronic realization of stress, syllable accent, and intonation. Therefore, the qualitative and quantitative characteristics of certain sounds must represent an entire group of elements in question. A natural question to ask, then, is how the distinctive features of all these elements are realized and combined. A point of reference for the model of this interaction could be a category of sound control/balance, interpreted in terms of F0 dynamics. The data presented in this paper allow us to consider the hypothesis that F0 change, viewed both in terms of paradigmatic and syntagmatic vectors, is the prerogative of phrasal intonation. The other two elements, namely word stress and syllable accents, are to be regarded as factors that regulate the balance of F0 change at the intersyllabic level. Word stress determines the syntagmatic distribution of tonal dynamics of this kind, whereas syllable accents determine the paradigmatic one.